Uji Daya Hambat Ekstrak Etanol Daun Mahkota Dewa (Phaleria macrocarpa Boerl.,) terhadap Bakteri Staphylococcus Aureus - Susi Novaryatiin; Nurul Chusna; Desti Amelia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The utilization of natural materials as a traditional medicine in Indonesia has recently increased, even some natural materials have been manufactured in fabrication on a large scale. The use of traditional medicine is considered to have fewer side effects compared with chemicals, besides that the price is more affordable. Besides other advantages of traditional medicine is the raw material is easy to obtain and the price is relatively cheap. Mahkota Dewa plant is often found and easily obtainable in Indonesia. Since the first, the efficacy of Mahkota Dewa as a medicinal plant is often used in society, especially leaves. Mahkota Dewa is believed to contain low natural chemical side-effects compared to other pharmaceutical drugs that make the Mahkota Dewa leaves the people's choice in traditional medicine. Mahkota Dewa has efficacy as an analgesic, antibacterial, and antihistamine drug. This study was aimed to determine the ability of inhibitory power of ethanolic extract of Mahkota Dewa leaves on Staphylococcus aureus bacteria based on the concentration of the extract. This research was conducted using Kirby-Bauer method that is diffusion method by using disc paper. The extraction process was carried out by percolation method with 96% ethanol solvent. The test was performed using 4 concentration variations with 3 repetitions. The results showed that ethanolic extract of Mahkota Dewa leaves was able to inhibit the growth of Staphylococcus aureus bacteria at tested concentrations of 1%, 5%, 10%, and 15% with inhibition zone was 8.3 ± 1.1 mm; 9.8 ± 1.9 mm; 11.6 ± 1.2 mm; and 13.1 ± 1.8 mm, respectively.